Evaluación de los refugios de vida silvestre de Manabí como potenciales atractivos turísticos - Vélez Mendoza, Angie Maibeth (2019)
The present work aimed to develop an assessment of the wildlife refuges of the province of Manabí as potential tourist attractions, a qualitative research with an exploratory-descriptive approach was used. Methodological design is covered by 4 phases depending on the specific objectives. On the first the tourist diagnosis was made, from which geographical, environmental, economic, social, basic services and infrastructure were obtained, which allowed to know the current situation of the areas and tourism management; this information was synthesized in a FODA matrix. The next phase is composed of the market study where catering and lodging services of San Lorenzo and San Vicente were characterized, presenting certain shortcomings when providing a quality service, through the Inventory sheet, 12 tourist resources were established, also the profile of the tourist and the main competitor of the protected areas being the Manglares, El Morro Wildlife Refuge. In the third phase the matrix tool of potentialities was applied, which established that in the REVSMC-Pacoche the main resources are San Lorenzo beach and the Pacoche Forest, while in the REVISECOF is Isla Corazón y Fragata, similarly, determining the potential tourist products to be developed which are: ecotourism, adventure and sports, rural tourism. In the last phase, 8 programmes and 14 projects were structured to solve the problems identified in this investigation.